THE EFFECTIVENESS OF SNOWBALL THROWING COOPERATIVE LEARNING MODEL ON STUDENTS' MATHEMATICS LEARNING OUTCOMES - Ofridaningsih, Ofridaningsih; Sumartono, Sumartono; Mokh. Anang, Herwanto (Journal of Education Technology and Inovation, 2023)
This study aims to determine the effectiveness of applying the snowball throwing learning model to the mathematics learning outcomes of class XI students at SMK N 3 Bondowoso. The design used is a one-group pretest-posttest design. The sample was obtained for class XI B SMK N 3 Bondowoso through random activities, namely random samples. Collecting data by testing student learning outcomes with five items for each pretest and posttest As for the data test of student learning outcomes using normal distribution, namely Kolmogorov-Smirnov and homogenity, The results showed a significant correlation of 0.000 <0.05, and the paired sample t test data also obtained a sig value of 0.000 <  0.05. That way there is influence or relationship between the pretest and the posttest, so that the snowball throwing model is effective on students' mathematics learning outcomes in class XI B SMK N 3 Bondowoso